The role of vitamin K in the pathology of newborns and infants (literature review) - Y.V. Marushko; A.O. Pysariev; T.V. Kurilina; O.A. Bovkun (Zaslavsky O.Yu., 2024)
The presented review considers modern views on the mechanism of development, prevention and treatment of vitamin K deficiency bleedings in newborns and infants. The search for literary sources was carried out in Scopus, Web of Science, Medscape, UpToDate, BioMed Central, The Cochrane Library, Embase, Google Scholar, PLoS Journals, PubMed databases. One of the main functions of vitamin K is the activation of coagulation factors II, VII, IX and X. The article examines the forms of hemorrhagic disease of newborns, their clinical manifestations and consequences. The history of the study on vitamin K role in hemorrhagic disorders is presented. The structure and forms of vitamin K, their role in the body is shown in detail. The article discusses approaches to the diagnosis of vitamin K deficiency bleedings, which include determination of prothrombin time, international normalized ratio and activated partial thromboplastin time. However, these laboratory tests have limited sensitivity and specificity. The most up-to-date approach is the study of proteins induced by vitamin K absence (PIVKA) whose levels increase with increasing severity of vitamin K deficiency. PIVKA II is used as a functional marker for the detection of vitamin K deficiency. The review also clarifies different regimens of parenteral and oral prophylaxis, as well as the experience of different countries on their use. Intramuscular administration of vitamin K is the standard for the prevention and treatment of hemorrhagic disease caused by vitamin K deficiency. The authors of the review noted that in 2019, the Association of Neonatologists of Ukraine signed a memorandum on the implementation of the European standards for the care of newborns EFCNI in Ukraine, according to which prophylactic administration of vitamin K is recommended for all newborns. For oral prevention of bleeding caused by vitamin K deficiency, one can use vitamin K1 (phytomenadione) manufactured by the Synergylab company - 2 mg orally at birth and then 1 mg orally every week for 3 months.